Knowledge and Practice about TT Vaccination among Undergraduate Female Medical Students - Basher, MS (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):520-23 The abstract of this article is available on the PubMed website